2020
DOI: 10.1155/2020/5864057
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acupuncture on Delayed‐Onset Muscle Soreness: A Systematic Review and Meta‐Analysis

Abstract: Objectives. Evidence for the effects of acupuncture on delayed-onset muscle soreness (DOMS) is inconsistent. The aim of this study was to explore the effects of acupuncture on DOMS. Methods. Studies investigating the effect of acupuncture on DOMS in humans that were published before March 2020 were obtained from eight electronic databases. The affected muscles, groups, acupuncture points, treatment sessions, assessments, assessment times, and outcomes of the included articles were reviewed. The data were extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
(131 reference statements)
0
11
0
2
Order By: Relevance
“…DOMS is described as delayed muscular pain resulting from muscular structure injury after training sessions or strenuous exercise, especially in eccentric contractions such as badminton [ 10 , 11 ]. Clinical symptoms and signs of DOMS include myalgia, tenderness, and decreased articular range of motion leading to unavoidable adverse effects on an athlete’s performance [ 10 ]. Signs and symptoms of DOMS increase progressively after exercise, peaking at 24–72 h post-exercise and gradually disappearing 5–7 days post-exercise.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…DOMS is described as delayed muscular pain resulting from muscular structure injury after training sessions or strenuous exercise, especially in eccentric contractions such as badminton [ 10 , 11 ]. Clinical symptoms and signs of DOMS include myalgia, tenderness, and decreased articular range of motion leading to unavoidable adverse effects on an athlete’s performance [ 10 ]. Signs and symptoms of DOMS increase progressively after exercise, peaking at 24–72 h post-exercise and gradually disappearing 5–7 days post-exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Signs and symptoms of DOMS increase progressively after exercise, peaking at 24–72 h post-exercise and gradually disappearing 5–7 days post-exercise. Although DOMS is not a serious problem, the associated discomfort can reduce participation in training sessions and/or sports performance [ 10 ]. Strategies to aid recovery when experiencing DOMS should be considered to reduce the risk of more severe injury during higher training loads or return to athletic competition following tapering and/or off-season [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental research such as RCTs for athletes, or systematic review based on it, can give a clear answer to the effectiveness of acupuncture. A recent systematic review of the effects of acupuncture treatment on DOMS reported that acupuncture had small-to-moderate effects compared to the no-treatment group and presented insufficient data for meta-analysis [66]. Further well-designed studies assessing acupuncture's efficacy in sports medicine are warranted to establish a strong evidence and to support clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 , 6 ] Previous studies showed the visual analog scale (VAS) and pressure pain threshold (PPT) to be the most common and reliable indicators of DOMS, in addition to blood and mechanical indicators such as serum CK and lactate dehydrogenase (LDH), surface electromyography, [ 7 ] and isokinetic peak torque. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%